Karin Baumgartner and Monika Shafi, editors. Anxious Journeys: Twenty-First-Century Travel Writing in German. Camden House, 2019. - Doris McGonagill (Studies in 20th & 21st Century Literature, 2020)
Review of Karin Baumgartner and Monika Shafi, editors. Anxious Journeys: Twenty-First-Century Travel Writing in German. Camden House, 2019. viii + 276 pp.
Keywords: Travel Writing; 21st Century; German